Female entrepreneurship: business, marriage and motherhood in England and Wales, 1851–1911. (2nd October 2019) - van Lieshout, Carry; Smith, Harry; Montebruno, Piero; Bennett, Robert J.
ABSTRACT: This article offers a new perspective on what it meant to be a business proprietor in Victorian Britain. Based on individual census records, it provides an overview of the full population of female business proprietors in England and Wales between 1851 and 1911. These census data show that around 30% of the total business population was female, a considerably higher estimate than the current literature suggests. Female entrepreneurship was not a uniform experience. Certain demographics clustered in specific trades and within those sectors employers and own-account proprietors had strikingly different age, marital status and household profiles. A woman's life cycle event such as marriage, motherhood and widowhood played an important role in her decision whether to work, the work available to her and the entrepreneurial choices she could make. While marriage and motherhood removed women from the labour force, they had less of an effect on their levels of entrepreneurship. Women who had young children were more entrepreneurial than those who had none, and entrepreneurship rates rose with the arrival of one child and continued to rise the more children were added to the family.